In Vitro Efficacy of Fungicides on Sclerotinia sclerotiorum and their Potential for Control of Stem Rot in Indian Mustard (Brassica juncea L.) - Bairwa, Shri Kishan; Lal Godara, Shanker; Meena, Susheela (International Journal of Bio-resource and Stress Management, 2015)
Sclerotinia stem rot or stem blight or white rot disease caused by Sclerotinia sclerotiorum (Lib.) de Bary is a serious problem in mustard crop in northern India. Efficacy of six fungicides, carbendazim 50 WP, propiconazole 25 EC, hexaconazole 5 EC, difenaconazole 25 EC, carbendazim 12%+mancozeb 63% 75WP and penconazole 10 EC were tested against S. sclerotiorum. Under in vitro studies, fungicides carbendazim 50 WP and carbendazim 12%+mancozeb 63% mixture 75 WP at 0.1% concentration completely inhibited the mycelial growth, sclerotial formation and germination of sclerotia. Propiconazole 25 EC, hexaconazole 5 EC, difenaconazole 25 EC, penconazole 10 EC were also found effective at higher concentration (0.05% and 0.1%) but at lower concentrations (less than 0.05%), these fungicides were observed less effective to inhibit the mycelial growth, sclerotial formation and germination of sclerotia. In field experiments during rabi 2007-08 and 2008-09, seed treatment with carbendazim 50 WP @ 2 g kg-1 and two foliar sprays of same at 0.1% was most effective for disease control and increased seed yield in both the years. In this treatment lowest disease incidence (9.32%), minimum disease intensity (7.50%), highest disease control (76.92%), maximum average production (14.89q ha-1) and maximum net profit as well as benefit-cost ratio (2.01:1) was recorded. Seed treatment with carbendazim 50 WP @ 2 g kg-1 and two foliar sprays of carbendazim 12%+mancozeb 63% 75 WP at 0.2% was also found effective in disease control (59.18%) and increased seed yield (12.96 q ha-1) over untreated control.